2016
DOI: 10.1186/s40409-016-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Paths to the discovery of antivenom serotherapy in France

Abstract: The current study presents a descriptive chronological survey of the articles published by Césaire Auguste Phisalix and Albert Calmette on snake poison, with the aim of shedding a light on the areas of research and reasoning followed by these scientists, leading up to their simultaneous discovery of antivenom serotherapy in 1894. The path taken by Phisalix is revealed in 15 articles that demonstrate the motivation of a naturalist and the way he confronted the puzzle of immunity against snake venom. In the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Interestingly, the production of specific antivenom was started by Vital Brazil in the 1900’s and it was Vital Brazil who also discovered the effectiveness of the polyvalent antivenom [87, 88]. At that time, antivenom was prepared with crude plasma of hyperimmunized animals.…”
Section: Potential Complement Of Antiophidic Serum Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the production of specific antivenom was started by Vital Brazil in the 1900’s and it was Vital Brazil who also discovered the effectiveness of the polyvalent antivenom [87, 88]. At that time, antivenom was prepared with crude plasma of hyperimmunized animals.…”
Section: Potential Complement Of Antiophidic Serum Therapymentioning
confidence: 99%
“…Nowadays, despite advances in the production of antivenoms, this production is still similar to the methods originally described by Vital Brazil [87, 88]. Currently, immunoglobulins or immunoglobulin fragments [F(ab’)2 or Fab] purified from serum are used in antivenom [2].…”
Section: Potential Complement Of Antiophidic Serum Therapymentioning
confidence: 99%
“…Von Bering and Kitasato in 1880 present their first work on serotherapy, showing that in the serum of animals immunized with diphtheria or tetanus toxins, there were specific elements of recognition for these toxins and that their use in patients conferred protection [2]. Later, Phlizalix and Calmette groups independently produce antisera against snake venoms [3], confirming the relevance of specific serum elements for the protective response. In those days, histological studies on organs of experimental animals subjected to immunization processes suggested that lymphoid organs were sites likely responsible for the synthesis of the serum elements responsible for protection against toxins and poisons [4].…”
Section: A Brief History On the B-cell Discoverymentioning
confidence: 99%
“…The conventional antivenom is generally produced from the blood of the large animals, frequently horses or sheep, immunized with the venom of a single snake or mixed venoms obtained from several animals to eliminate the intraspecific diversification [7]. Nevertheless, the serum used to treat snakebite victims may cause various side effects, such as anaphylactic shock, pyrogen reaction and serum sickness, which are mainly caused by the nonspecific proteins found in commercially available antivenoms [811].…”
Section: Introductionmentioning
confidence: 99%